Comparative analysis of the performance of relational and non-relational databases in applications implemented in C# - Patryk Baliński; Łukasz Chudy; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
The article focuses on comparing relational and non-relational databases using applications written in C#. The aim of the study is to understand in which cases relational databases are preferred and when it is worth considering the use of non-relational databases. The research examines the speed of data retrieval, updating, and deletion, in the context of five different databases, including relational ones like PostgreSQL, MySql, Oracle, and non-relational ones such as Neo4j and MongoDB. The data consists of 1,578,098 records. In the case of relational databases, a unified database model was applied, while in NoSQL databases, the data model was appropriately adjusted to the specific type of non-relational database. Differences in the execution time of database queries are analyzed based on indexing strategies and query complexity. Special attention is given to query performance efficiency in the context of using C# and libraries that facilitate the connection between the application and databases. The conducted research indicates that the PostgreSQL database achieves the lowest average query response times.